KOMPETENSI APARATUR DESA DALAM PENGELOLAAN PEMBANGUNAN DESA DI DESA BULUDE KECAMATAN KABARUAN - RANTO, FRANHEID FREDI (JURNAL ADMINISTRASI PUBLIK, 2022)
This research was conducted to find out how to empower the management of village development inBulude village, Kabaruan district. This study uses a type of qualitative research. The theory used thereare six aspects contained in the concept of competence, namely knowledge, understanding, abilities,values, attitudes and interests. Data collection techniques used in this study are: Interview,Observation, and Documentation of data obtained from various sources and then analyzed whichbecomes a conclusion from the research process. The results obtained from this study indicate that thelimitations regarding knowledge of village development management by village officials are everyadministrative action related to village development management starting from the performance of theapparatus and village development management procedures based on applicable laws and regulations.Regarding the competence of the village apparatus, secondly, he must know and understand his dutiesand functions as a village apparatus. The third thing that is very important is related to thecompetence of village officials in managing village development, namely knowing and understandingthe procedures for formulating policies related to the management of village development.